2007
DOI: 10.1007/s11721-007-0007-8
|View full text |Cite
|
Sign up to set email alerts
|

Moving targets: collective decisions and flexible choices in house-hunting ants

Abstract: Many decisions involve a trade-off between commitment and flexibility. We show here that the collective decisions ants make over new nest sites are sometimes sufficiently flexible that the ants can change targets even after an emigration has begun. Our findings suggest that, in this context, the ants' procedures are such that they can sometimes avoid 'negative information cascades' which might lock them into a poor choice. The ants are more responsive to belated good news of a higher quality nest than they are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…Both species can select the best nest site even if news of it arrives late in the decision-making process Franks et al 2007b). However, there are some differences between the two collective decision-making systems.…”
Section: Decision-making In Social Insect Coloniesmentioning
confidence: 99%
See 1 more Smart Citation
“…Both species can select the best nest site even if news of it arrives late in the decision-making process Franks et al 2007b). However, there are some differences between the two collective decision-making systems.…”
Section: Decision-making In Social Insect Coloniesmentioning
confidence: 99%
“…Experimental (Franks et al 2007b) and theoretical work has examined the robustness of social insects' collective decision-making to this kind of late information. Our analysis shows how such robustness might be understood because under the direct-switching model, once all scouts are committed and no further information on new alternatives can arrive, decisionmaking proceeds optimally between the available alternatives based on their quality: the only departure from optimality is the bias in the starting point of the decision process based on the relative discovery times of the alternatives.…”
mentioning
confidence: 99%
“…In a different study on Temnothorax albipennis, involving multiple target options which increased the degree of complexity for the ants, colony splitting was observed. When the preferred nest was degraded after relocation had been initiated, only 15% of the colonies were able to switch their choice and occupy the new target nest and 22% of the colonies split between the available options (Franks et al, 2007). In a study on T. albipennis dealing with quorum sensing, it was found that these ants do not switch back from carrying to tandem running (Pratt, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…How organisms respond to a midway change has hardly been explored (but see Franks et al, 2007). In the present study, we analyse the flexibility of the relocation process.…”
Section: Introductionmentioning
confidence: 99%
“…The quorum threshold itself is not modulated depending on the quality of the new nest [30]. If nest quality is artificially manipulated during the assessment phase of an emigration, the ants are able to respond flexibly to the new nest qualities; if quality is manipulated after quorum is reach and implementation has begun, then colonies often become 'trapped' in an inferior nest [15], [?]. This indicates that quality is not re-assessed after quorum has been reached in these cavity-dwelling Temnothorax species.…”
Section: Quorum Sensing In House-hunting Antsmentioning
confidence: 99%